2017
DOI: 10.1111/bjhp.12248
|View full text |Cite
|
Sign up to set email alerts
|

If you needed an organ transplant would you have one? The effect of reciprocity priming and mode of delivery on organ donor registration intentions and behaviour

Abstract: Reciprocal altruism may be a useful tool in increasing intentions to join the organ donor register. Further evaluation is required to determine whether this increase in intention can be translated into organ donation behaviour. Statement of contribution What was already known? Demand for organs in the United Kingdom far outstrips supply, so finding strategies to increase registration on the organ donor register could save hundreds of lives per year. Despite the majority of people in the United Kingdom agreeing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
(23 reference statements)
0
19
0
Order By: Relevance
“…These ideas gained some support in a pilot study which showed that medical students' intentions to donate were higher following exposure to a VRA message (Landry, 2006). Developing on this, O'Carroll, Haddow, Foley, andQuigley (2017) and showed that nonregistered participants exposed to a VRA message, compared to controls, reported greater intentions to register. The effect of VRA on behaviour (donor registration) was demonstrated by the results from a large scale (1 million participants) trial comparing nine different messages on UK driving license application web pages.…”
Section: Blood and Organ Donation 38mentioning
confidence: 97%
“…These ideas gained some support in a pilot study which showed that medical students' intentions to donate were higher following exposure to a VRA message (Landry, 2006). Developing on this, O'Carroll, Haddow, Foley, andQuigley (2017) and showed that nonregistered participants exposed to a VRA message, compared to controls, reported greater intentions to register. The effect of VRA on behaviour (donor registration) was demonstrated by the results from a large scale (1 million participants) trial comparing nine different messages on UK driving license application web pages.…”
Section: Blood and Organ Donation 38mentioning
confidence: 97%
“…Since a preliminary report of this study was published [ 29 ], the reciprocity message has been tested by other researchers with similarly positive effects. In Scotland, a similar reciprocity message increased intentions to join the ODR compared to controls, in particular when delivered online as opposed to face to face [ 30 ], providing further support for the use of the reciprocity message for online government platforms. Both sets of findings support Landry’s [ 21 ] feasibility study, making salient the potential reciprocal nature of the decision to join the ODR.…”
Section: Discussionmentioning
confidence: 99%
“…We tested a question-behavior effect with or without affective attitudes, assessing whether completion of affective attitude items reduces intention to donate, but including dummy items to overcome the mere measurement (question-behavior) effect. Two modalities of intervention delivery were tested to determine if a social desirability effect, i.e., being in the presence of an interviewer, masks the effects of including affective attitudes on intention to donate [21].…”
Section: Methodsmentioning
confidence: 99%